2011
DOI: 10.1080/00206814.2010.504076
|View full text |Cite
|
Sign up to set email alerts
|

Geodynamics of the Amirante Ridge and Trench Complex, Western Indian Ocean

Abstract: The formation and evolution of the ∼600 km long arcuate Amirante Ridge and Trench Complex (ARTC) is a significant geomorphic-structural feature in the Western Indian Ocean (WIO). The WIO contains evidence of at least two major magmatic episodes followed by continental rifting within the span of a little more than 20 million years. This involved the splitting of Madagascar from India at around 85 Ma and then separation between India and the Seychelles at 64-63 Ma as a possible consequence of two powerful volcan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…During the period 89 and 85 Ma, as Indian plate passed over the Marion plume, Madagascar separated from India (Agarwal et al 1992;Storey et al 1995) leading to conjugate spreading along the Mascarene and Palitana Ridges. By integrating seismic refraction and reflection, free-air gravity, magnetic anomaly data, and Ar dating of rocks, Mukhopadhyay et al (2012) opined that spreading along the Palitana Ridge split the Laxmi Ridge and Seychelles from India (between 79 and 66 Ma). Further, Samal et al (2012) from studies of high resolution seismic, free-air gravity and well data in the west coast of India suggested that the gravity low along the Laxmi Ridge is due to the down-warping at the lower crust as a result of excessive magmatic material below the ridge.…”
Section: Introductionmentioning
confidence: 98%
“…During the period 89 and 85 Ma, as Indian plate passed over the Marion plume, Madagascar separated from India (Agarwal et al 1992;Storey et al 1995) leading to conjugate spreading along the Mascarene and Palitana Ridges. By integrating seismic refraction and reflection, free-air gravity, magnetic anomaly data, and Ar dating of rocks, Mukhopadhyay et al (2012) opined that spreading along the Palitana Ridge split the Laxmi Ridge and Seychelles from India (between 79 and 66 Ma). Further, Samal et al (2012) from studies of high resolution seismic, free-air gravity and well data in the west coast of India suggested that the gravity low along the Laxmi Ridge is due to the down-warping at the lower crust as a result of excessive magmatic material below the ridge.…”
Section: Introductionmentioning
confidence: 98%
“…These discontinuities are expected to have profound effects on ridge petrology, melt dynamics, and evolution of the seafloor (Gregg, Behn, Lin, & Grove, ; Iyer & Ray, ; Klein & Langmuir, ; Langmuir, Bender, & Batiza, ; Lin & Morgan, ; Macdonald, Scheirer, & Carbotte, ; Mukhopadhyay & Iyer, ; Mukhopadhyay, Iyer, Ray, Karisiddaiah, & Drolia, ; Ray, Iyer, Banerjee, Misra, & Widdowson, ; Tolstoy, Harding, & Orcutt, ). Also the northern Indian Ocean floor was perforated in the geological past by at least four major mantle plumes, two plumes apiece contributed in the making of the eastern and the western continental margins of India (Mukhopadhyay, Karisiddaiah, & Ghosh, ; Todal & Edholm, ). Among these, while the Marion and Reunion plumes contributed significantly to the formation of western continental margin of India, the other two, Kerguelen and Crozet plumes, influenced the construction of the eastern continental margin.…”
Section: Introductionmentioning
confidence: 99%
“…In fact between 90 and 85 million years (Ma), the first episode of flood basalt volcanism occurred along the western margin of the north‐moving Indian Plate (then positioned in the southern hemisphere) when the Marion Plume erupted. This volcanism prompted the separation of Madagascar from India (Agrawal, Pandey, & Negi, , Mahoney, Duncan, Khan, Gnos, & McCormick, ; Mukhopadhyay et al, ). The second episode of basalt volcanism in the north‐western Indian Ocean had been from the Reunion plume.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The western continental margin has several ridge-like features, which run parallel to the coast and also have significantly controlled the sedimentation pattern along the margin. The architecture of this margin seems to have been affected by three events-two episodes of continental separation associated with episodic eruptions from two plumes-the older Marion Plume in the south and the younger Reunion in the north, and the Deccan volcanism (Mukhopadhyay et al 2012). …”
mentioning
confidence: 97%